2000
DOI: 10.1002/1531-8249(200009)48:3<297::aid-ana3>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage in Alzheimer's disease varies with apolipoprotein E genotype

Abstract: Brain metabolism and the activity of the α‐ketoglutarate dehydrogenase complex (KGDHC), a mitochondrial enzyme, are diminished in brains from patients with Alzheimer's disease (AD). In 109 subjects, the Clinical Dementia Rating (CDR) score was highly correlated with brain KGDHC activity. In AD patients who carried the epsilon 4 allele of the apolipoprotein E gene (ApoE4), the CDR score correlated better with KGDHC activity than with the densities of neuritic plaques or neuritic tangles. In contrast, in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(72 citation statements)
references
References 50 publications
1
71
0
Order By: Relevance
“…However, mitochondrial dysfunction in AD appears to vary by APOE genotype, with greater dysfunction in APOE e4 carriers. 10 There is significant evidence that degradation fragments of the apoE4 protein have a greater neurotoxic effect on mitochondrial function over time compared to apoE3 or apoE2 fragments. [28][29][30][31] These fragments, found in cultured neuronal cells and AD brain, induce neurofibrillary tangle-like structures and cause neurotoxicity in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mitochondrial dysfunction in AD appears to vary by APOE genotype, with greater dysfunction in APOE e4 carriers. 10 There is significant evidence that degradation fragments of the apoE4 protein have a greater neurotoxic effect on mitochondrial function over time compared to apoE3 or apoE2 fragments. [28][29][30][31] These fragments, found in cultured neuronal cells and AD brain, induce neurofibrillary tangle-like structures and cause neurotoxicity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Declines in key brain mitochondrial TCA enzymatic activities in AD patients have been well documented and associated with APOE e4 status. 9,10 Insulin is critically important in peripheral and central energy metabolism and serves to regulate blood glucose levels. Insulin is transported across the blood/brain barrier and peripheral levels of insulin tend to correlate with levels in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction was described in patients with AD, especially in those with the apoE4 genotype (143). Previously, we showed that apoE avidly binds to the ␣-and ␤-subunits of mitochondrial F1-ATPase (144), suggesting a possible role for apoE in intracellular transport within or between cell organelles.…”
Section: Apoe4 Neuropathology Independent Of A␤ Apoe Cleavage In Neurmentioning
confidence: 96%
“…4). It contains both the positively charged receptor binding region (amino acids [136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] and the hydrophobic lipid binding region (amino acids 240-270). Mutagenesis of four conserved residues in the lipid binding region or three conserved positively charged residues in the receptor binding region abolished the neurotoxicity of apoE4 .…”
Section: Apoe4 Neuropathology Independent Of A␤ Apoe Cleavage In Neurmentioning
confidence: 99%
“…The reduction in KGDHC activities in brains from AD patients bearing one apolipoprotein E4 allele is highly correlated to a clinical dementia rating (12). Reduced KGDHC activity is also found in fibroblasts from some AD patients (13).…”
mentioning
confidence: 92%